Contested Landscapes and Local Voice - A. Dan Tarlock (Washington University Journal of Law & Policy, 2000)
This Essay identifies four common elements in the many ad hoc efforts currently being pursued. These elements are not exhaustive, but taken together they suggest that United States land use controls are evolving in a new and important direction. The first element is pre-legal because it is the formulation of a new vision of a community not recognized in the existing legal structure. The second and third are legal actions that extend existing land use and other local regulatory options to increase local community voice in all the determinants of landscape change. The fourth element is post-legal. Communities are turning to new consensus-based governance processes to overcome obstacles in the existing legal system.
Keywords: City planning and redevelopment law; Land use